The ethics of Devatma - Kanal, Satewan Parsram (Munshiram Manoharlal Publishers for Dev Samaja, Moga, 1974)
On the religious philosophy of Satyanand Agnihotri (Dev Atma), 1850-1929, who seceded from the Brahmo Samaj and founded a parallel Hindu socioreligious society, Dev Samaj; a study.